Kurikulum Satuan Pendidikan: Konsep, Tantangan, dan Evaluasi dalam Dunia Pendidikan Indonesia - Salsabila Andhini Malika Putri; Nabilla Utari; Sela Pesta Kristina Simatupang; Givaen Ray Simanjutak; Muhammad Saputra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The School-Based Curriculum (KSP) is an operational curriculum developed by educational units to align learning objectives with the characteristics of students, local potentials, and the evolving needs of society. KSP provides schools with autonomy to develop curricula that are relevant to their local context, allowing for variations in the approach to learning. This article aims to discuss the basic concept of KSP, the challenges in its implementation, and its evaluation in the context of Indonesian education. The research method used is a literature review, analyzing theories and regulations related to KSP. The results show that KSP plays a strategic role in providing schools with the flexibility to develop curricula that meet the needs of the region and students. However, the implementation of KSP still faces various challenges, such as limited teacher competencies, insufficient understanding of curriculum principles, and weak evaluation and supervision of curriculum implementation. To address these challenges, the evaluation of KSP implementation needs to be strengthened by improving teachers' competencies, developing relevant learning materials, and enhancing ongoing curriculum supervision. By doing so, KSP can be optimized to achieve better educational outcomes in Indonesia.